Vital Problems of Primary and Secondary Schools and Solution Suggestions: A Qualitative Analysis Based on the Opinions of School Administrators - Gulay ASLAN (Anı Publishing, 2021)
Based on the opinions of school administrators, this study aimed to identify the vital problems of primary and secondary schools and suggest solutions to these problems. It was designed with a multiple case study method from qualitative research approaches. The study group consisted of 35 school administrators working in primary and secondary schools in Tokat province in the 2016-2017 academic year. The data were collected by interview technique. During the interviews, demographic information about school administrators as well as information on the problems of schools were collected. The data were analyzed by content analysis technique. In data collection, processing, and analysis processes, measures to increase validity and reliability were taken. In the research, 38 problems were identified under five themes related to the problems experienced in primary and secondary schools. Twelve of these problems were found to be of "vital" importance. The first three of the vital problems of the schools in the study group were 'lack of funding for schools', 'insufficient physical infrastructure of schools', and 'parents lack of interest in school'. It is recommended that the Ministry of National Education pays attention to the voices coming from the schools, reestablish the balance of authority responsibility, switch to school-based budgeting, and allocate funds to each school.